The Freedom of Conscience and the Freedom of Association in the Spanish Constitution of 1812 - Rojas Buendía, María del Mar (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2015)
It is an opportune moment to discuss the separation of state and religion, i.e., the necessary delimitation between the public and the private sectors, given the current transcendence they seem to enjoy. This invites us to review the historical and legal precedents of the rights of freedoms of conscience and association